2013
DOI: 10.3945/jn.112.164038
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing Obese Zucker Rats with Niacin Induces the Transition of Glycolytic to Oxidative Skeletal Muscle Fibers

Abstract: In the present study, we tested the hypothesis that niacin increases the oxidative capacity of muscle by increasing the oxidative type I muscle fiber content. Twenty-four obese Zucker rats were assigned to 2 groups of 12 rats that were fed either a control diet (O group) or a diet supplemented with 750 mg/kg diet niacin (O+N group) for 4 wk. In addition, one group of lean rats (L group) was included in the experiment and fed the control diet for 4 wk. Plasma and liver concentrations of TG were markedly greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 42 publications
5
62
3
Order By: Relevance
“…In addition, we observed that the expression of genes involved in fatty acid transport, mitochondrial fatty acid import and oxidation, oxidative phosphorylation and angiogenesis in skeletal muscle is elevated by niacin administration [7], indicating a change of the muscle metabolic phenotype towards a more oxidative one. Moreover, we found that genes encoding molecular regulators of muscle fiber distribution, like peroxisome proliferator-activated receptor δ (PPARδ), PPARγ coactivator-1α (PGC-1α) and PGC-1β, are strongly induced by niacin in skeletal muscle of the obese Zucker rats [7]. Up-regulation of these transcription factors by niacin administration is likely responsible for the muscle fiber switch from type II to type I because PPARδ and PGCs are critical regulators of muscle fiber distribution and muscle metabolic phenotype [8][12].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…In addition, we observed that the expression of genes involved in fatty acid transport, mitochondrial fatty acid import and oxidation, oxidative phosphorylation and angiogenesis in skeletal muscle is elevated by niacin administration [7], indicating a change of the muscle metabolic phenotype towards a more oxidative one. Moreover, we found that genes encoding molecular regulators of muscle fiber distribution, like peroxisome proliferator-activated receptor δ (PPARδ), PPARγ coactivator-1α (PGC-1α) and PGC-1β, are strongly induced by niacin in skeletal muscle of the obese Zucker rats [7]. Up-regulation of these transcription factors by niacin administration is likely responsible for the muscle fiber switch from type II to type I because PPARδ and PGCs are critical regulators of muscle fiber distribution and muscle metabolic phenotype [8][12].…”
Section: Introductionmentioning
confidence: 84%
“…At pharmacological doses (2–6 g/d), niacin has long been used for the clinical therapy of different forms of dyslipidemia, particularly hypertriglyceridemia, in humans due to the fact that niacin has potent lipid-modulating activities (lowering of triacylglycerols (TAG), LDL-cholesterol, and lipoprotein (a), increasing HDL-cholesterol) [1][5]. Apart from these lipid-modulating effects of niacin, which have been suggested to involve inhibition of lipolysis in adipose tissue [4], and reduction of gene expression of APOC3, which is known to inhibit hydrolysis of VLDL-TAG, in the liver [6], niacin was also recently reported to have pronounced effects on skeletal muscle gene expression and skeletal muscle phenotype in obese Zucker rats [7]. Using this genetic model of obesity, metabolic syndrome and diabetes, we observed that administration of a pharmacological dose of niacin for 4 wk causes a muscle fiber shift from type II (glycolytic) to type I (oxidative) in skeletal muscle [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In experiments in obese rats it could be demonstrated that niacin increases the FFAs utilization of muscles which may play a role in its TG-lowering effect (Ringseis et al 2013).…”
Section: Mechanisms Of Action Of Niacinmentioning
confidence: 99%